CONTROL OF ADIPOSE-TISSUE LIPOLYSIS IN ECTOTHERM VERTEBRATES - Migliorini, R. H.; Limaverde, J. S.; Machado, C. R.; Cardona, GMP; Garofalo, MAR; Kettelhut, I. C. (Amer Physiological Soc, 1992)
Lipolytic activity of fish (Hoplias malabaricus), toad (Bufo paracnemis), and snake (Philodryas patagoniensis) adipose tissue was investigated in vivo and in vitro. Catecholamines or glucagon did not affect the release of free fatty acids (FFA) by incubated fish and toad adipose tissue. Catecholamines also failed to activate snake adipose tissue lipolysis, which even decreased in the presence of epinephrine. However, glucagon stimulated both the lipolytic activity of reptilian tissue in vitro and the mobilization of FFA to plasma when administered to snakes in vivo. The release of FFA from incubated fish, amphibian, and reptilian adipose tissue increased markedly in the presence of cAMP or xanthine derivatives, inhibitors of phosphodiesterase. Forskolin or fluoride, activators of specific components of the adenylate cyclase system, strongly stimulated toad adipose tissue lipolysis. The data suggest that adipocyte triacylglycerol lipase of ectotherm vertebrates is activated by a cAMP-mediated phosphorylation and that the organization of the membrane-bound adenylate cyclase system is similar to that of mammals.
Keywords: FISH; Toad; SNAKE; FREE FATTY ACIDS; GLYCEROL; CAMP; XANTHINE DERIVATIVES; FORSKOLIN; F-; Catecholamines; GLUCAGON